Effect of compressive stress on the ferroelectric hysteresis behavior in 0-3 PMN-PT/cement composites - N. Jaitanong (2018)
Lead magnesium niobate titanate (PMN-PT)Portland cement (PC) composites were produced. PMN- PT amount used in this work were 30, 50, and 70% by volume. The effects of PMN-PT content (using 30%, 50%, 70% PMN-PT) and stress on the ferroelectric polarization-electric field (P-E) hysteresis of the composites are reported in this present work. From the results, it was found that there was an increase in the instantaneous remnant polarization (Pir) when PMN- PT amount increased while Pirwas found to decrease when the stress was increased from 0 to 57 MPa. Copyright © Taylor & Francis Group, LLC.